Surface-asymmetric carbon-based hydrogel photothermal conversion material as well as preparation method and application thereof

By preparing surface asymmetric carbon-based hydrogels, combined with carbon-polyvinyl alcohol hydrogels and temperature phase conversion cellulose, the problems of complex preparation and poor stability of existing gel materials are solved, efficient water evaporation and long-term stability are achieved, and suitable for seawater desalination and wastewater purification.

CN119842108APending Publication Date: 2025-04-18NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510077925.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing production process of asymmetric gel materials on the upper and lower surfaces is complex, and the structure and performance are prone to change during long-term water evaporation, affecting the efficiency of seawater desalination.

Method used

The carbon-polyvinyl alcohol hydrogel is combined with cellulose with temperature phase transition characteristics, and the surface asymmetric carbon-based hydrogel is prepared by freeze-thaw cycle and light treatment to form a hydrophilic and asymmetric Janus structure to enhance the photothermal conversion efficiency and stability.

Benefits of technology

It improves the water evaporation rate and photothermal conversion efficiency, maintains long-term stability, is suitable for industrial production, and is suitable for seawater desalination and wastewater purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842108A_ABST
    Figure CN119842108A_ABST
Patent Text Reader

Abstract

The invention discloses a surface-asymmetric carbon-based hydrogel photothermal conversion material as well as a preparation method and application thereof, and belongs to the technical field of photothermal conversion materials. The method comprises the following steps: dissolving a carbon-based compound and a polyvinyl alcohol monomer in deionized water to obtain a corresponding suspension, and carrying out freezing and thawing cycles for a certain number of times to obtain carbon-based polyvinyl alcohol hydrogel; and uniformly coating the surface of the carbon-based-polyvinyl alcohol hydrogel material with a cellulose solution with a temperature phase transition characteristic to obtain the surface-asymmetric carbon-based hydrogel photo-thermal conversion material. The photothermal conversion material disclosed by the invention can be converted from a hydrophilic surface to a hydrophobic surface after absorbing heat and raising temperature under illumination, so that an asymmetric Janus structure is formed, and the photothermal conversion material has efficient photothermal conversion capability, high water transmission rate and excellent long-term stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of photothermal conversion materials, and relates to a surface asymmetric carbon-based hydrogel photothermal conversion material, and also relates to a preparation method of the photothermal conversion material and an application of the photothermal conversion material. Background Art

[0002] Rapid population growth, climate change and environmental pollution have made the shortage of clean fresh water one of the most severe challenges in the world. As a green and efficient technology, solar-driven water evaporation is widely used in fields such as seawater desalination and wastewater purification to alleviate the global water shortage problem. The high specific surface area, porous structure and adjustable chemical composition of gel materials also make them show great potential in applications such as solar steam generation, water purification and desalination.

[0003] However, in the process of solar water evaporation to remove impurities, insufficient solar energy absorption, heat loss, and salt crystal aggregation caused by long-term exposure to salt water limit the steam generation rate, thereby reducing the efficiency of seawater desalination. So far, the design of layered nanostructured gels, double-layer evaporators, surface engineering and other structures has provided ideas for improving the evaporation rate of photothermal interfaces. However, the existing asymmetric gel materials with upper and lower surfaces are often composed of different layers stacked together, and the preparation process is complicated; and the good surface hydrophilicity of gel evaporators will affect the water evaporation performance; in addition, their structure and performance are also very easy to change during the long-term water evaporation process. Summary of the invention

[0004] The embodiments of the present application provide a surface asymmetric carbon-based hydrogel photothermal conversion material, which has efficient photothermal conversion capability, fast water transfer rate and excellent long-term stability.

[0005] The present invention also provides a method for preparing a surface asymmetric carbon-based hydrogel photothermal conversion material, which has simple preparation steps and is suitable for industrial rapid production.

[0006] The present invention also provides applications of the surface asymmetric carbon-based hydrogel photothermal conversion material, which can be applied to seawater desalination and wastewater purification under photothermal effect.

[0007] In order to achieve the above object, the technical solution of the embodiment of the present invention is:

[0008] In a first aspect, an embodiment of the present invention provides a surface asymmetric carbon-based hydrogel photothermal conversion material, which includes a carbon-based-polyvinyl alcohol hydrogel and cellulose loaded on the carbon-based-polyvinyl alcohol hydrogel, wherein the cellulose has a temperature phase transition characteristic.

[0009] In combination with the first aspect, in a possible implementation manner, the carbon-based-polyvinyl alcohol hydrogel is formed by cross-linking a carbon-based compound and polyvinyl alcohol.

[0010] In combination with the first aspect, in a possible implementation, the carbon-based compound includes one or more of carbon nanotubes, graphene oxide, MXene titanium carbide nanosheets, and carbon black.

[0011] In combination with the first aspect, in a possible implementation, the cellulose includes one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, and hydroxypropyl methyl cellulose.

[0012] In a second aspect, an embodiment of the present invention provides a method for preparing a surface asymmetric carbon-based hydrogel photothermal conversion material, comprising the following steps:

[0013] Step S1: dissolving a carbon-based compound and a polyvinyl alcohol monomer in deionized water to obtain a corresponding suspension, and obtaining a carbon-based polyvinyl alcohol hydrogel after a certain number of freeze-thaw cycles;

[0014] Step S2: Coating cellulose with temperature phase transition characteristics on the surface of the carbon-based-polyvinyl alcohol hydrogel, and obtaining a surface asymmetric carbon-based hydrogel photothermal conversion material after irradiation with light.

[0015] In combination with the second aspect, in a possible implementation, in step S1, the concentration of the carbon-based compound is 1.0-50.0 mg / mL, and the concentration of the polyvinyl alcohol monomer is 0.1-0.4 g / L.

[0016] In combination with the second aspect, in a possible implementation, in step S1, during the thawing cycle, the freezing temperature is -30 to -20°C, the freezing time is 6-9 hours, the thawing time is 0.5-2 hours, and the number of freeze-thaw cycles is 3-5 times.

[0017] In combination with the second aspect, in a possible implementation, in step S2, the concentration of the cellulose is 0.1-2.0 wt %.

[0018] In a third aspect, an embodiment of the present invention provides an application of the surface asymmetric carbon-based hydrogel photothermal conversion material as described above or the surface asymmetric carbon-based hydrogel photothermal conversion material obtained by the preparation method as described above, and the surface asymmetric carbon-based hydrogel photothermal conversion material is used for seawater desalination and wastewater purification under the photothermal effect.

[0019] One or more technical solutions provided in the embodiments of the present invention have at least the following technical effects or advantages:

[0020] 1) In the surface asymmetric carbon-based hydrogel photothermal conversion material of the present invention, the cellulose coated on the surface of the hydrogel has excellent thermosensitive behavior. At room temperature, cellulose with abundant hydroxyl groups interacts with water molecules through hydrogen bonds, which not only enhances the hydrophilicity of the gel, but also improves the absorption capacity of sunlight and the efficiency of heat energy transfer; when sunlight irradiates the surface of the gel, cellulose absorbs heat, and its structure realizes a coil-sphere transformation. This transformation makes the originally hydrophilic carbon-based hydrogel surface hydrophobic, resulting in a Janus structure with asymmetric hydrophilicity and hydrophobicity, making it easier for water molecules to overflow, which improves the water evaporation photothermal conversion efficiency of the gel; in addition, the hydrophilic layer can also cooperate with the hydrophobic surface to adjust the distribution and evaporation rate of water, making it difficult for salt to accumulate on the surface of the gel; at the same time, the rough and irregular surface characteristics of the gel caused by the phase change of cellulose also cause the incident light to be scattered in multiple directions, which increases the possibility of light absorption, so that solar light can be better utilized.

[0021] 2) According to the preparation method provided by the present invention, a carbon-based gel material is first prepared by aqueous solution polymerization, and then a cellulose solution with temperature phase transition characteristics is coated on the surface of the gel. After washing with deionized water and irradiating with sunlight, a carbon-based hydrogel photothermal conversion material with a rough surface and an irregular structure is obtained. The preparation process is simple and easy to operate, and is suitable for industrial production and promotion.

[0022] 3) The surface asymmetric carbon-based hydrogel photothermal conversion material of the present invention can be directly used as a highly efficient, salt-resistant and stable solar steam generator in the field of large-scale seawater desalination and sewage purification to alleviate the shortage of fresh water resources and solve the problem of water pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 This is a cross-sectional SEM image of the surface asymmetric carbon-based hydrogel photothermal conversion material prepared in Example 1 of the present application;

[0025] Figure 2 The contact angle diagram of the surface of the surface asymmetric carbon-based hydrogel photothermal conversion material prepared in Example 1 of the present application at different temperatures;

[0026] Figure 3 The water evaporation rate of the surface asymmetric carbon-based hydrogel photothermal conversion material prepared in Example 1 of the present application under sunlight illumination;

[0027] Figure 4 This is a stability evaluation diagram of the evaporation rate of the surface asymmetric carbon-based hydrogel photothermal conversion material prepared in Example 1 of the present application in a continuous 100-hour test;

[0028] Figure 5 This is a comparison chart of the removal rates of four types of ions in seawater by the surface asymmetric carbon-based hydrogel photothermal conversion material prepared in Example 1 of the present application as a solar light absorber. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] It should be noted that all raw materials in the embodiments of the present invention can be purchased on the market or prepared according to conventional methods known to those skilled in the art; "first" and "second" in the embodiments of the present invention are only used for descriptive purposes and cannot be understood as indicating or implying relative importance; the groups in the embodiments of the present invention should be understood as the general meaning in the chemical field, for example: groups usually refer to atomic groups, including all "functional groups" in the structure of organic matter, specifically including hydrogen, fluorine, chlorine, bromine, iodine, alkyl, alkenyl, alkynyl, methoxy, phenyl, acyl, carboxyl, carbonyl, nitro, hydroxyl, sulfonic acid, etc. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present invention can be understood according to specific circumstances.

[0031] The invention provides a surface asymmetric carbon-based hydrogel photothermal conversion material, which comprises a carbon-based polyvinyl alcohol hydrogel and cellulose loaded on the carbon-based polyvinyl alcohol hydrogel, wherein the cellulose has a temperature phase transition characteristic.

[0032] According to the present invention, the carbon-based-polyvinyl alcohol hydrogel is formed by cross-linking a carbon-based compound and polyvinyl alcohol.

[0033] Exemplarily, the carbon-based compounds include carbon nanotubes, graphene oxide, MXene titanium carbide nanosheets (Ti3C2T X ), one or a mixture of at least two of carbon black.

[0034] Illustratively, the cellulose includes one or a mixture of at least two of hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, and hydroxypropyl methyl cellulose.

[0035] In the surface asymmetric carbon-based hydrogel photothermal conversion material of the present invention, the cellulose coated on the surface of the hydrogel has excellent thermosensitive behavior. At room temperature, cellulose with abundant hydroxyl groups interacts with water molecules through hydrogen bonds, which not only enhances the hydrophilicity of the gel, but also improves the absorption capacity of sunlight and the efficiency of heat energy transfer. When sunlight irradiates the surface of the gel, the cellulose absorbs heat and the temperature rises, and its structure realizes a coil-sphere transformation. This transformation makes the originally hydrophilic carbon-based hydrogel surface hydrophobic, resulting in a Janus structure with asymmetric hydrophilicity and hydrophobicity, making it easier for water molecules to overflow, which improves the water evaporation photothermal conversion efficiency of the hydrogel. In addition, the hydrophilic layer can also cooperate with the hydrophobic surface to adjust the distribution and evaporation rate of water, making it difficult for salt to accumulate on the surface of the gel. At the same time, the rough and irregular surface characteristics of the gel caused by the phase change of cellulose also cause the incident light to be scattered in multiple directions, which increases the possibility of light absorption and enables solar light to be better utilized.

[0036] The surface asymmetric carbon-based hydrogel photothermal conversion material of the present invention has a photothermal conversion efficiency of more than 80% under one sunlight intensity, and a water evaporation rate of 2.8-3.5 kg m -2 h -1 After 10 hours of light exposure in a 20 wt% NaCl solution, no salt was precipitated from the gel surface. The gel could evaporate continuously for 100 hours and maintain a water evaporation rate of 2.5-3.5 kg m -2 h -1 , with high light-to-heat conversion efficiency, fast water transfer efficiency and excellent long-term stability during use.

[0037] The present invention provides a method for preparing a surface asymmetric carbon-based hydrogel photothermal conversion material, which specifically comprises the following steps:

[0038] Step S1: dissolving the carbon-based compound and polyvinyl alcohol monomer in deionized water to obtain a corresponding suspension, and obtaining a carbon-based polyvinyl alcohol hydrogel after a certain number of freeze-thaw cycles.

[0039] Step S2: Coating cellulose with temperature phase transition characteristics on the surface of the carbon-based polyvinyl alcohol hydrogel, and obtaining a surface asymmetric carbon-based hydrogel photothermal conversion material after irradiation with light.

[0040] Preferably, in step S1, the concentration of the carbon-based compound is 1.0-50.0 mg / mL, and the concentration of the polyvinyl alcohol monomer is 0.1-0.4 g / L.

[0041] Exemplarily, in the preparation method, the carbon-based compound includes but is not limited to carbon nanotubes, graphene oxide, MXene titanium carbide nanosheets (Ti3C2T X), carbon black or a mixture of at least two thereof. Cellulose includes, but is not limited to, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, or a mixture of at least two thereof.

[0042] Preferably, in step S1, during the freeze-thaw cycle, the freezing temperature is -30 to -20°C, the freezing time is 6-9 hours, the thawing time is 0.5-2 hours, and the number of freeze-thaw cycles is 3-5 times.

[0043] Preferably, in step S2, the concentration of cellulose is 0.1-2.0 wt%.

[0044] Illustratively, in step 2, the cellulose solution can be coated on the surface of the carbon-based-polyvinyl alcohol hydrogel by spin coating, drop coating, dip coating, scraping coating, spraying, etc. The present invention does not limit the coating method.

[0045] An embodiment of the present invention provides an application of the surface asymmetric carbon-based hydrogel photothermal conversion material as described above or the surface asymmetric carbon-based hydrogel photothermal conversion material obtained by the above preparation method, and the surface asymmetric carbon-based hydrogel photothermal conversion material is applied to seawater desalination and wastewater purification.

[0046] In order to enable the above-mentioned implementation details and operations of the present application to be clearly understood by those skilled in the art, and to significantly reflect the progressiveness of the surface asymmetric carbon-based hydrogel photothermal conversion materials, preparation methods and applications of the embodiments of the present application, the above-mentioned technical scheme is illustrated by means of multiple embodiments below.

[0047] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples are conventional biochemical reagents unless otherwise specified. The experimental methods are conventional methods unless otherwise specified.

[0048] Example 1

[0049] This embodiment provides a method for preparing a surface asymmetric carbon-based hydrogel photothermal conversion material, which is as follows:

[0050] (1) A certain mass of MXene titanium carbide nanosheets was weighed into deionized water and ultrasonically dispersed to obtain a 30.0 mg / mL MXene dispersion. Then, 1.0 g of polyvinyl alcohol was dissolved in 6 mL of the above MXene dispersion and stirred at 90 °C for 3 h.

[0051] (2) The dispersion obtained in step (1) was poured into a double-sided glass container and sealed. The molded sample was frozen in a refrigerator at -23°C for 8 hours, then thawed at room temperature for 30 minutes, and the freeze-thaw cycle was repeated 3 times to obtain a MXene-polyvinyl alcohol hydrogel.

[0052] (3) Prepare a 1.0 wt% hydroxymethyl cellulose aqueous solution.

[0053] (4) Spray 1 mL of the 1 wt% hydroxymethyl cellulose solution prepared in step (3) onto the surface of the MXene-polyvinyl alcohol hydrogel. After standing for 3 hours, the solution is completely absorbed. After washing with deionized water and irradiating with light, a surface asymmetric carbon-based hydrogel photothermal conversion material is obtained.

[0054] Figure 1 This is a cross-sectional SEM image of the surface asymmetric carbon-based hydrogel photothermal conversion material prepared by the preparation method of Example 1. As can be seen from the figure, there is an obvious thin film on the upper surface of the carbon-based hydrogel material, which proves that cellulose has been evenly coated on the surface of the hydrogel. In addition, there are a large number of pores in the cross-section of the carbon-based gel material, which promotes the transmission and evaporation of water and enhances the photothermal conversion effect. At the same time, the presence of the pore structure provides a diffusion channel for the salt in the seawater, so that the salt can be discharged from the hydrogel system in time with the evaporation of water, avoiding the accumulation of salt inside the hydrogel, thereby ensuring the salt resistance and long-term stability of the hydrogel.

[0055] Figure 2 The contact angles of the surface asymmetric carbon-based hydrogel photothermal conversion material prepared in Example 1 at different temperatures. As can be seen from the figure, at room temperature, cellulose with abundant hydroxyl groups interacts with water molecules through hydrogen bonds, which not only enhances the hydrophilicity of the gel, but also improves the absorption capacity of sunlight and the efficiency of heat energy transfer. After being irradiated by sunlight, cellulose absorbs heat and produces a coil-sphere structural transformation, which causes the hydrophilic state of the gel surface to change from hydrophilic to hydrophobic. This transformation causes the upper and lower surfaces of the gel to have asymmetric hydrophilicity, which makes it easy for water molecules to overflow, thereby improving the water evaporation photothermal conversion efficiency of the gel.

[0056] Figure 3 The water evaporation rate of the surface asymmetric carbon-based hydrogel photothermal conversion material prepared in Example 1 under one sunlight illumination. As can be seen from the figure, the hydrogel photothermal conversion material has a water evaporation rate of >3.0 kg / m under one sunlight illumination. -2 h -1 evaporation rate.

[0057] Figure 4 The stability of the evaporation rate of the surface asymmetric carbon-based hydrogel photothermal conversion material prepared in Example 1 during a continuous 100-hour test is evaluated. Figure 4 It can be seen that the evaporation rate of the hydrogel photothermal conversion material remains almost unchanged under 100 hours of continuous irradiation with high intensity sunlight, which demonstrates the highly stable photothermal evaporation performance of the hydrogel photothermal conversion material.

[0058] Figure 5 The removal rate of four ions in seawater by the surface asymmetric carbon-based hydrogel photothermal conversion material prepared in Example 1 as a solar light absorber. As can be seen from the figure, under a simulated sunlight intensity, after solar light photothermal evaporation purification, the salt ion concentration in the purified water dropped sharply compared with the initial seawater, and the concentration of each ion in the purified water was all lower than the water quality standard specified by the World Health Organization, meeting the requirements for drinking water. This proves that the photothermal conversion material has a very excellent ion removal ability and can be applied to the field of wastewater purification.

[0059] Example 2

[0060] This embodiment provides a method for preparing a surface asymmetric carbon-based hydrogel photothermal conversion material, which is as follows:

[0061] (1) A certain mass of graphene oxide was weighed and dissolved in deionized water, and then ultrasonically dispersed to obtain a 9.0 mg / mL graphene oxide dispersion. Then, 1.5 g of polyvinyl alcohol was dissolved in 8 mL of the graphene oxide dispersion, and stirred at 70° C. for 4 hours.

[0062] (2) The dispersion obtained in step (1) was poured into a double-sided glass container and sealed. The molded sample was frozen in a refrigerator at -25°C for 7 hours, then thawed at room temperature for 1 hour, and the freeze-thaw cycle was repeated 3 times to obtain graphene oxide-polyvinyl alcohol hydrogel.

[0063] (3) Prepare a 2.0 wt% hydroxyethyl cellulose solution.

[0064] (4) 1 mL of 2.5 wt% hydroxyethyl cellulose prepared in step (4) was dropped onto the surface of the graphene oxide-polyvinyl alcohol hydrogel obtained in step (2), and the solution was spread flat with a spatula. After standing for 5 hours, the solution was completely absorbed, and after washing and irradiation, a surface asymmetric carbon-based hydrogel photothermal conversion material was obtained.

[0065] Example 3

[0066] The preparation method of the surface asymmetric carbon-based hydrogel photothermal conversion material proposed in this embodiment is as follows:

[0067] (1) A certain amount of carbon black prepared by chemical method was weighed and dissolved in deionized water, and ultrasonically dispersed to obtain a 6.0 mg / mL carbon black dispersion. Then, 1.0 g of polyvinyl alcohol was dissolved in 5 mL of the above carbon black dispersion and stirred at 90° C. for 2 hours.

[0068] (2) The dispersion obtained in step (1) was poured into a double-sided glass container and sealed. The molded sample was frozen in a refrigerator at -30°C for 5 hours, and then thawed at room temperature for 30 minutes. The freeze-thaw cycle operation was repeated 5 times to obtain a carbon black-polyvinyl alcohol hydrogel.

[0069] (3) Prepare a 1.5 wt% hydroxypropyl cellulose aqueous solution.

[0070] (4) Spin coating 200 μL of 1.5 wt% hydroxypropyl cellulose prepared in step (3) onto the surface of the carbon black-polyvinyl alcohol hydrogel obtained in step (2) at 3000 rpm for 30 seconds, and repeat 5 times. Then, the solution was allowed to stand for 6 hours until it was completely absorbed, and the surface asymmetric carbon-based hydrogel photothermal conversion material was obtained after washing with deionized water and irradiation with light.

[0071] Example 4

[0072] This example refers to the preparation method of Example 1, except that the only difference is that the type of cellulose used in step (3) is different, namely, 2.5 wt% of hydroxypropyl cellulose.

[0073] Example 5

[0074] This example refers to the preparation method of Example 2, except that the coating method of the cellulose added in step (4) is different. This example adopts a dipping method.

[0075] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other. Each embodiment focuses on the differences from other embodiments.

[0076] The above embodiments are only used to illustrate the technical solutions of the present application, but not to limit the present application. Although the present application is described in detail with reference to the above embodiments, it should be understood by those skilled in the art that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features thereof can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the present application.

Claims

1. A surface asymmetric carbon-based hydrogel photothermal conversion material, characterized in that: The invention comprises a carbon-based polyvinyl alcohol hydrogel and cellulose loaded on the carbon-based polyvinyl alcohol hydrogel, wherein the cellulose has a temperature phase transition characteristic.

2. The photothermal conversion material according to claim 1, characterized in that: The carbon-based-polyvinyl alcohol hydrogel is formed by cross-linking a carbon-based compound and polyvinyl alcohol.

3. The photothermal conversion material according to claim 2, characterized in that: The carbon-based compound includes one or more of carbon nanotubes, graphene oxide, MXene titanium carbide nanosheets, and carbon black.

4. The photothermal conversion material according to claim 1, characterized in that: The cellulose includes one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose and hydroxypropyl methyl cellulose.

5. A method for preparing a surface asymmetric carbon-based hydrogel photothermal conversion material, characterized in that: The following steps are involved: Step S1: dissolving a carbon-based compound and a polyvinyl alcohol monomer in deionized water to obtain a corresponding suspension, and obtaining a carbon-based polyvinyl alcohol hydrogel after a certain number of freeze-thaw cycles; Step S2: Coating cellulose with temperature phase transition characteristics on the surface of the carbon-based-polyvinyl alcohol hydrogel, and obtaining a surface asymmetric carbon-based hydrogel photothermal conversion material after irradiation with light.

6. The preparation method according to claim 5, characterized in that: In the step S1, the concentration of the carbon-based compound is 1.0-50.0 mg / mL, and the concentration of the polyvinyl alcohol monomer is 0.1-0.4 g / L.

7. The preparation method according to claim 5, characterized in that: In the step S1, during the freeze-thaw cycle, the freezing temperature is -30 to -20°C, the freezing time is 6-9 hours, the thawing time is 0.5-2 hours, and the number of freeze-thaw cycles is 3-5 times.

8. The preparation method according to claim 5, characterized in that: In the step S2, the concentration of the cellulose is 0.1-2.0 wt%.

9. An application of the surface asymmetric carbon-based hydrogel photothermal conversion material according to any one of claims 1 to 4 or the surface asymmetric carbon-based hydrogel photothermal conversion material obtained by the preparation method according to any one of claims 5 to 8, characterized in that: The surface asymmetric carbon-based hydrogel photothermal conversion material is applied to seawater desalination and wastewater purification.